THE STRESS LEVEL OF CLASS 2021 KOAS STUDENTS IS ODD DURING CHILDREN'S DENTAL TREATMENT - Utami, Sri Pandu Pandu; Sari, Tika Bonita (E-Jurnal Medika Udayana, 2025)
: Dentistry is considered a stressful job. As dentists have close contact with patients. Increased stress can affect the dentist's performance which can be a major threat to the patient's physical and mental health. General dentistry students are required to pass theoretical and practical courses in pediatrics within a short period of time. Stress among dental students occurs from different sources and affects them differently, and has sometimes been shown to have a significant negative effect on their performance. Purpose : to find out Is the stress level of class 2021 coas students odd during child dental care ? Methods : This type of research is descriptive observation with a cross sectional design . Results: The results of the research that has been done show that the stress level experienced by co-ass students in the IKGA RSGM Baiturrahmah Lab has a low stress level of 70%. The highest level of stress was in the low category, i.e. 12 female respondents (70.6%) and 2 male respondents (66.7%) . The average (mean) of the 8 questions shows that the answer to the question about " Injection of local anesthetic in anxious children" has the highest average of 5.50%. Conclusion: In general, the stress experienced by co-ass students in the IKGA Lab at RSGM Baiturrahmah has a low level of stress and is mostly experienced by female students. The highest average question is the level of stress is the injection of local anesthetic in anxious children .